Exponential Stability of Periodic Solutions for Inertial Type BAM Cohen-Grossberg Neural Networks - Chunfang Miao; Yunquan Ke (Abstract and Applied Analysis)
The existence and exponential stability of periodic solutions for inertial type BAM Cohen-Grossberg neural networks are investigated. First, by properly choosing variable substitution, the system is transformed to first order differential equation. Second, some sufficient conditions that ensure the existence and exponential stability of periodic solutions for the system are obtained by constructing suitable Lyapunov functional and using differential mean value theorem and inequality technique. Finally, two examples are given to illustrate the effectiveness of the results.